2016
DOI: 10.3238/arztebl.2016.0203
|View full text |Cite|
|
Sign up to set email alerts
|

Health and Disease at Age 100: Findings From the Second Heidelberg Centenarian Study

Abstract: German centenarians experienced a substantial number of ill nesses, dominated by sensory and mobility conditions. Cardiovascular diseases were the only potentially lethal illnesses with high prevalence. Evidence of unaddressed pain seems alarming, requiring future research. Emerging health profiles indicate that even in very advanced age, quality of life may be improved by enhanced diagnostics and optimal disease management. Mobility limitations may be addressed with preventive efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…This percentage is expected to be even higher in individuals aged 100 and more years old. A recent study with a sample of German centenarians, for instance, showed that more than 70% of the participants reported at least one fall since age the 95 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This percentage is expected to be even higher in individuals aged 100 and more years old. A recent study with a sample of German centenarians, for instance, showed that more than 70% of the participants reported at least one fall since age the 95 …”
Section: Introductionmentioning
confidence: 99%
“…Data from international studies show the presence of a variety of medical conditions in centenarians, with cardiovascular (e.g., heart disease), musculoskeletal (e.g., arthritis) and neurological (e.g., dementia) diseases as being the most frequent. 3 Due to these chronic health problems and often comorbid sensory deficits (namely vision and hearing) and mobility problems (balance and poor walking), the probability of incurring a fall is expected to be higher with advancing age. The World Health Organization's most recent report on falls prevention in older age revealed that approximately 28-35% of people aged 65 and over fall each year, a percentage that increases to 32-42% for those over 70 years of age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present Heidelberg Dental Centenarian Study (HD100Z) was designed as a cross-sectional, population-based survey and clinical examination among persons born before 1920, living in a defined area in South-Western Germany. Taking into account the feasible patient recruitment achieved by previous centenarian studies (Biagi et al, 2017;Jopp, Boerner, & Rott, 2016;Kaufman et al, 2014) and due to the exploratory nature of the study, the sample size was set at 50 study participants. The study received ethical approval by the Medical Ethics Committee (S-168/2019) and was registered with the German Clinical Trials Register (DRKS 00017128).…”
Section: Me Thodsmentioning
confidence: 99%
“…The study sample was drawn from the population-based Second Heidelberg Centenarian Study. 10 The institutional review board of the Faculty of Behavioral and Cultural Studies at Heidelberg University approved the study. For the purpose of the present article, we selected participants (N 5 78) for whom data on centenarian EOL thoughts from the centenarian and a proxy informant were available.…”
Section: Samplementioning
confidence: 99%